2007
DOI: 10.1071/ch06461
|View full text |Cite
|
Sign up to set email alerts
|

Uncatalyzed Reactions in Aqueous Media: Three-Component, One-Pot, Clean Synthesis of Tetrahydrobenzo[b]pyran Derivatives

Abstract: The synthesis of various tetrahydrobenzo[b]pyran derivatives has been carried out by means of an uncatalyzed, three-component, one-pot clean condensation of aromatic aldehydes, reactive methylene compounds, and dimidone in aqueous medium. Simple workup, and mild and neutral conditions that give quantitative yields of products in pure form, are the attractive features of this method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…The NMR parameters are in agreement with those found in the literature. 31 Synthesis of Deuterated 1,2-BuS. 1,2-BuS-1,1-d 2 and 1,2-BuS-2-d 1 were synthesized from the corresponding oxides, i.e., 1,2-butylene oxide-1,1-d 2 and 1,2-butylene oxide-2-d 1 .…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The NMR parameters are in agreement with those found in the literature. 31 Synthesis of Deuterated 1,2-BuS. 1,2-BuS-1,1-d 2 and 1,2-BuS-2-d 1 were synthesized from the corresponding oxides, i.e., 1,2-butylene oxide-1,1-d 2 and 1,2-butylene oxide-2-d 1 .…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…A detailed literature survey towards the multicomponent synthesis of tetrahydrobenzo[b]pyran revealed that most of the protocols employed for this reaction operate under high thermal activation [14][15][16][17][18][19], microwave activation [15,20,21] and ultrasonic irradiation [22,23]. Recently, Fotouhi et al [24] reported electrochemical synthesis of tetrahydrobenzo[b]pyran.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the tetrahydrobenzo[b]pyran nucleus is an important structural motif of a series of natural products [8,9] and can be converted into pyridine systems which relate to pharmacologically important calcium antagonists of the dihydropyridine(DHP) [10,11] type. The importance of these compounds has led the scientific community to synthesize them using the bicomponent condensation [12,13] of dimedone with a-cyanocinnamonitriles or multicomponent condensation [14][15][16][17][18][19] of dimedone with aromatic aldehydes and malononitrile.…”
Section: Introductionmentioning
confidence: 99%
“…Also, epoxides can be converted to thiiranes in reaction with different sulfur donor reagents such as thiourea, dimethylthioformamide, inorganic thiocyanates, phosphine sulfide and 3‐methylbenzothiazol‐2‐thione . Often these reactions take place in the presence of various acidic or basic catalysts . Thiiranes as important precursors have been also used for various purposes …”
Section: Introductionmentioning
confidence: 99%